Frontal Sinus Fractures: 10-Year Contemporary Experience at a Level 1 Urban Trauma Center. Issue 4 (12th June 2021) - Obayemi, Adetokunbo; Losenegger, Tasher; Long, Sallie; Spielman, Daniel; Casiano, Michael F.; Reeve, Gwendolyn; Kacker, Ashutosh; Stewart, Michael; Sclafani, Anthony
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Frontal sinus fractures account for 5% to 15% of all facial fractures, and have traditionally been associated with high kinetic energy blunt injury. Surgical management is largely focused on minimizing potentially serious sequelae including frontal sinus dysfunction, CSF leak, and significant cosmetic deformity. An institutional database of 1944 patients presenting with maxillofacial fractures over a 10-year period was queried. Demographics, mechanism of injury, yearly trends, surgical approaches, and follow-up data were examined. A total of 160 (8.3%) patients presented with at least 1 fracture of the frontal sinus anterior table, posterior table, or frontal sinus outflow tract during the study period. The average annual number of cases was 15.9 ± 5.7 per year with a peak of 21.5 ± 4.0 cases during the 2014 to 2015 period and a decline to 8.5 ± 1.5 cases/year from 2016 to 2017. Among those patients with falls, 61.5% (n = 40) were a result of tripping or fainting at a height of <6 ft. 55.6% of fracture types were isolated to the anterior table, but fracture location was not significantly associated with operative intervention. Cases of operative fracture type had a higher rate of both displacement and comminution compared to nonoperative fractures ( P < 0.00001). Of all patients presenting with frontal sinus fractures, 75% of cases were managed nonoperatively. However, many patients presented with falls and other seemingly low energy injuries which are not traditionally associated with frontal sinus trauma. These results highlight the need for continued follow-up even in otherwise low-risk urban populations in order to avoid long term sinus dysfunction.